Multicomponent synthetic polymers with viral-mimetic chemistry for nucleic acid delivery. - Soliman, M; Nasanit, R; Abulateefeh, SR; Allen, S; Davies, M; Briggs, S; Seymour, L; Preece, J; Grabowska, A; Watson, SA; Alexander, C (2012)
The ability to deliver genetic material for therapy remains an unsolved challenge in medicine. Natural gene carriers, such as viruses, have evolved sophisticated mechanisms and modular biopolymer architectures to overcome these hurdles. Here we describe synthetic multicomponent materials for gene delivery, designed with features that mimic virus modular components and which transfect specific cell lines with high efficacy. The hierarchical nature of the synthetic carriers allows the incorporation of membrane-disrupting peptides, nucleic acid binding components, a protective coat layer, and an outer targeting ligand all in a single nanoparticle, but with functionality such that each is utilized in a specific sequence during the gene delivery process. The experimentally facile assembly suggests these materials could form a generic class of carrier systems that could be customized for many different therapeutic settings.